2023
DOI: 10.7150/thno.80307
|View full text |Cite
|
Sign up to set email alerts
|

TCRαβ+NK1.1-CD4-CD8- double-negative T cells inhibit central and peripheral inflammation and ameliorate ischemic stroke in mice

Abstract: Background: Excessive immune activation leads to secondary injury and impedes injured brain recovery after ischemic stroke. However, few effective methods are currently used for equilibrating immune balance. CD3 + NK1.1 -TCRβ + CD4 -CD8 -double-negative T (DNT) cells which do not express NK cell surface markers are unique regulatory cells that maintain homeostasis in several immune-related diseases. However, the therapeutic potential and regulatory mechanism of DNT cells in ischemic stroke are still unknown. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Previous findings by our group demonstrated that a higher CCR5 was expressed in DNT [ 19 ]. To investigate how transferred DNT migrate into skin tissue, we performed transcriptome sequencing on the skin from control and IMQ-treated mice.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous findings by our group demonstrated that a higher CCR5 was expressed in DNT [ 19 ]. To investigate how transferred DNT migrate into skin tissue, we performed transcriptome sequencing on the skin from control and IMQ-treated mice.…”
Section: Resultsmentioning
confidence: 91%
“…DNT highly express CCR5, which is critical for DNT migration and function [ 19 ]. In our study, we also observed significantly increased CCL3/4 (CCR5 ligands) expression in the inflamed skin tissue of mice with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke, comprising lacunar infarction, cardioembolic, and large artery atherosclerosis subtypes, represents a significant medical challenge [ 28 ]. T lymphocytes play a pivotal role in the pathophysiology of ischemic stroke, regulating the immune response and inflammatory processes in the body [ 52 ]. A comprehensive investigation into the dynamic changes of T lymphocytes following ischemic stroke revealed an increase in peripheral T lymphocyte numbers post-event [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCL25 in thymus chemoattracted DCs [36]. CD3 + NK1.1 − TCRβ + CD4 − CD8 − double-negative T (DNT) cells enhance Treg cell recruitment through CCL5 in ischemic stroke lesions [37]. Transendothelial DCs chemoattracted by endothelial ligand, CX3CL1, might help the thymus actively acquire blood-borne antigens to induce and maintain central tolerance [38].…”
Section: Discussionmentioning
confidence: 99%